Transanal Approach to Rectal Polyps and Cancer - Rai, Vinay; Mishra, Nitin (Clinics in Colon and Rectal Surgery, 2016)
A transanal approach to rectal polyp and cancer excision is often an appropriate alternative to conventional rectal resection, and has a lower associated morbidity. There has been a steady evolution in the techniques of transanal surgery over the past 30 years. It started with traditional transanal excision and was revolutionized by introduction of transanal endoscopic microsurgery in early 1980s. Introduction of transanal minimally invasive surgery made it more accessible to surgeons around the world. Now robotic platforms are being tried in certain institutions. Concerns have been raised about recurrence rates of cancers with transanal approach and success of subsequent salvage operations.
Keywords: transanal excision; transanal endoscopic microsurgery; transanal minimally invasive surgery; local excision; rectal polyp